Interferensi Bahasa Dalam Interaksi Jual Beli Di Pasar Cikampek Serta Relevansinya Sebagai Media Pembelajaran Whiteboard Animation - Habibah, Nur; Rosalina, Sinta; Nuraini, Cut (Peneliti.net, 2024)
The aims of this study are to 1) describe the forms of interference of words, phrases and clauses in buying and selling interactions at the Cikampek market; 2) describe the factors that cause interference in buying and selling interactions at the Cikampek market; and 3) relevance of research results as learning media of whiteboard animation negotiating text in class X high school. To answer the formulated problems, the researcher used a descriptive method. The subjects used in this study were adults and parents in the Cikampek market. The object of this research was obtained from a utterance in the form of Sundanese interference with Indonesian between people in the Cikampek market area. This study focuses on interference analysis at the sentence level, which is related to the use of word fragments, phrases, and clauses. The results showed that there was interference from Sundanese to Indonesian in buying and selling interactions at the Cikampek market and found 37 words, 33 phrases and 7 clauses that experienced interference. The factors that cause interference in buying and selling interactions at the Cikampek market are interlingual factors and the transfer of language structures. Furthermore, the results of this study are used as learning media for negotiating text in the form of whiteboard animation videos. Whiteboard animation negotiating text learning media can be viewed via the link https://youtu.be/LkdQ0HxRzcM .